Understanding North Korea: Rimjin-gang Citizen Journalists Out to Cure the “Sick Man of Asia”? - Suzy Kim (Japan Focus)
Back in 2008, a small but significant piece of news circulated in South Korea about a magazine "secretly published by North Korean journalists" as one headline read. But this it hardly covered in the Western media, and it seems the news has finally reached across the Pacific with the publication of the magazine's first English edition in October 2010. On the evening of October 18, 2010 Ishimaru Jiro - editor and publisher of Rimjin-gang magazine1 - was invited to speak at the Arthur L. Carter Journalism Institute at NYU in "a discussion about journalism in and about North Korea" (according to the event flyer). The Nation published an article on November 15, 2010, seductively titled "North Korea's Citizen Journalism" featuring the publication.With years of experience reporting on North Korea, Ishimaru launched Rimjin-gang in 2007. Published twice a year in South Korea and Japan in their respective languages, it is edited in Seoul by North Korean defector, Choi Jin-i, before being translated into Japanese and then from Japanese into English.2 Rimjin-gang aims to publish reports about everyday life in North Korea with the help of a dozen underground North Korean informants, whom Ishimaru identifies as "North Korean journalists." I have opted to use the term "informant" instead, given serious misgivings about whether they can be called journalists. This is a central issue as explained in the body of this essay. The magazine is important to evaluate for several reasons. Not only does it claim to be "the first magazine about North Korea written by North Koreans" (The Nation), but it is also touted as "the first publication to create a channel for two-way communication between the divided Korean people," as exemplified by the title "Rimjin-gang" - the name of the river that flows across the De-Militarized Zone dividing the north and south.This article is an attempt to engage in a critical conversation about how we know what we know about North Korea, reflecting upon the historical and structural conditions that configure the way North Korea is known and understood by those outside North Korea.